2019
DOI: 10.1155/2019/2106741
|View full text |Cite
|
Sign up to set email alerts
|

Load Transfer Characteristics of a Cable Bolt in DEPT

Abstract: Cable bolts help surrounding rock masses of underground excavations to form internal rock structure and thus self-stabilize through effective load transfer between rock masses and cable bolts. The load transfer characteristics of cable bolt play the most significant role in cable selection for support design. There are many factors potentially affecting the load transfer characteristics of cable bolt via strengthening or weakening load contributors such as cable bonding, mechanical interlocking, frictional res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…As suggested by Figs. 13, 14, and 15, the effect of rotation on the cable pull-out load was relatively small and similar to the findings of Li (2019). This was more evident in the larger diameter cables compared to the smaller cable such as the Superstrand cable.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…As suggested by Figs. 13, 14, and 15, the effect of rotation on the cable pull-out load was relatively small and similar to the findings of Li (2019). This was more evident in the larger diameter cables compared to the smaller cable such as the Superstrand cable.…”
Section: Resultssupporting
confidence: 69%
“…Thomas (2012), Chen et al (2015), , and Hagan and Li (2017) conducted studies on the various characteristics of cable bolts using a Modified Laboratory Short Encapsulation Pull Test (MLSPET). Aziz et al(2016) and Li (2019) reported on a series of pull-out tests on cable bolts using the Minova Axially Split Embedment Apparatus (MASEA). This setup used the double embedment concept of SSPT with the unequal embedment length concept of the LSEPT.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern resembles the sinking behavior observed in the roof displacement (see Figure 6). The deformation of the roof's surrounding rock and the tensile deformation of the moving traction anchor cable contribute to the gradual increase in axial load (Jahromi et al, 2011;Li et al, 2019;Shi et al, 2019). However, under the combined influence of the self-supporting capacity of the surrounding rock and the growing constraints provided by anchor cable support, the deformation speed of the surrounding rock is controlled and exhibits a gradual decrease (see Figure 6), corresponding to a reduction in the rate of increase for the axial load of the anchor cable.…”
Section: Analysis Of Evolution Of Anchor Cable Loadmentioning
confidence: 99%
“…Experiments are unanimously stating the fact that the stronger grout, the higher the pullout load is expected [10], [25]- [27]. Also, the longer curing time results in higher strength; however, similar to other cementitious materials, the strength increases logarithmically, and 99% of the strength is usually achieved after 28 days [28]- [30]. This paper introduces a newly developed laboratory equipment that enables static and dynamic pullout tests of tendons under static and dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 99%